2009
DOI: 10.4049/jimmunol.0802536
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Functional P-Selectin Ligand Exacerbates Salmonella Serovar Typhimurium Infection

Abstract: The selectin family of adhesion molecules mediates the recruitment of immune cells to the site of inflammation, which is critical for host survival of infection. To characterize the role of selectins in host defense against Salmonella Typhimurium infection, wild-type (WT) mice and mice lacking P-selectin glycoprotein ligand-1 (PSGL-1), P-, E-, or L-selectin, or the glycosyltransferase C2GlcNAcT-I (core 2) were infected using a Salmonella acute gastroenteritis model. Mice were monitored for survival and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Platelets also utilize PSGL-1 to adhere to vasculature [30], suggesting that it is important for formation of cellular complexes that function in pathogen clearance. For example, PSGL-1/P-selectin interactions are critical for neutrophil recruitment and host defense against Salmonella typhimurium [31]. However, microbes can also escape immune responses by targeting selectin-binding by PSGL-1.…”
Section: Psgl-1 and Cell Migrationmentioning
confidence: 99%
“…Platelets also utilize PSGL-1 to adhere to vasculature [30], suggesting that it is important for formation of cellular complexes that function in pathogen clearance. For example, PSGL-1/P-selectin interactions are critical for neutrophil recruitment and host defense against Salmonella typhimurium [31]. However, microbes can also escape immune responses by targeting selectin-binding by PSGL-1.…”
Section: Psgl-1 and Cell Migrationmentioning
confidence: 99%
“…Furthermore, recent studies have shown that adhesion molecules, such as PSGL1, CD34, and fractalkine, are important in the intestinal innate immune response against enteric infections [152-154]. Infected mice lacking PSGL-1 or P-selectin with C. rodentium , a mouse pathogen which reproduces the disease seen with the human pathogens EPEC and EHEC [123], showed a more pronounced morbidity associated with higher bacterial load, elevated IL-12 p70, TNF-alpha, IFN-gamma, MCP-1 and IL-6 production, and more severe inflammation than the WT mouse [152, 155]. Likewise, infected mice lacking core 2 (O-glycosylation), PSGL-1, or P-selectin with Salmonella , showed a more pronounced morbidity and a significantly higher mortality rate associated with higher bacterial load and proinflammatory cytokine production than the WT control mouse [130].…”
Section: Class-2 Spates the Lectin-like Immunomodulatory Serine Protmentioning
confidence: 99%
“…Despite the pro‐inflammatory environment detected into the colonic LP of PSGL‐1 −/− mice, these animals do not spontaneously develop intestinal inflammation or ulcerative colitis (UC). However, it has been reported that in the absence of PSGL‐1, mice are highly sensitive to pathogens such as Salmonella 17. It is therefore possible that the impaired leukocyte recruitment in PSGL‐1 KO mice may prevent the surveillance of immune cells on overgrowth and inflammation induced by commensal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PSGL‐1 is involved in the recruitment of leukocytes to the ileum, in an animal model of CD 13, 14, and also to the intestinal lamina propria (LP) 15, 16. In addition, PSGL‐1 deficiency increases the severity of acute gastroenteritis induced by Salmonella typhimurium infection, with an enhanced synthesis of pro‐inflammatory cytokines 17. All these data suggest a role of PSGL‐1 in the regulation of the immune responses in the gut.…”
Section: Introductionmentioning
confidence: 99%